Development of melt electrohydrodynamic 3D printing for complex microscale poly (ε-caprolactone) scaffolds. (18th August 2016) - He, Jiankang; Xia, Peng; Li, Dichen
Abstract: The replication of native hierarchical structures into synthetic scaffolds is important to direct cell growth and tissue regeneration. However, most of the existing scaffold strategies lack the capability to simultaneously realize the controlled fabrication of macroscopic geometries as well as microscale architectures with the scale similar to living cells. Here we developed a melt electrohydrodynamic printing platform and verified its feasibility to fabricate three-dimensional (3D) tissue-engineered scaffolds with complex curved geometries and microscale fibrous structures. Melting temperature was studied to stably print poly ( ε -caprolactone) (PCL) filaments with the size of about 10 μ m, which was precisely stacked into 3D straight walls with fine surface quality. By adjusting stage moving speed and directions, 3D PCL scaffolds with curved contours and predefined fiber orientations or spacing were successfully printed. Biological experiments showed that the printed microscale scaffolds had good biocompatibility and facilitated cellular proliferation and alignment in vitro . It is envisioned that the melt electrohydrodynamic printing can potentially provide an innovative tool to fabricate hierarchical scaffolds that mimic the native tissue architectures in a multiscale level.